Anticancer, Antioxidant and Antimicrobial Evaluation of Cr (III) and Rh(III) Complexes Derived from A New Mannich Base - Ahmed, Alya'a J.; Alias, Mahasin F. (Iraqi Journal of Science, 2024)
The Mannich base ligand was synthesized in an ethanol medium through a condensation reaction of 2-mercaptobenzimidazole and ciprofloxacin at room temperature. Subsequently, several metal complexes of this ligand were prepared. To characterize both the base ligand and the metal complexes, various techniques were employed, including elemental analysis, FT-IR spectroscopy, UV-Vis spectroscopy, molar conductivity measurements, magnetic moment determination, and melting point analysis. The results were shown that the metal complexes formed have the formula [Cr(L)2Cl2] Cl.H2O and [Rh(L)2(H2O)2] Cl3.H2O, where L= mannich base ligand. Based on spectroscopic analytical, coordination with metal ions involves the 'N' donor atom of mannich base and 'N' atom of piprizaing ring, and two complexes are A six-coordinated octahedral structure is suggested. Molar conductivity of these complexes showed that they were electrolytic in nature. In this study, the anticancer and antioxidant potential of the Mannich base ligand and its metal complexes were investigated against MDA-MB-231 cell lines  and using the DPPH free radical scavenging assay. Moreover, the in vitro efficacy of the ligand and its complexes against Gram-negative bacteria (E. coli) and Gram-positive bacteria (Staphylococcus aureus), as well as the fungal strain Candida albicans, was evaluated using the disc diffusion method. The results indicated that Cr (III) and Rh(III) complexes demonstrated the highest levels of cytotoxicity against MDA-MB-231 cell lines, enhances antioxidant and antimicrobial activity more than the free ligand. These findings suggest that these metal complexes may have promising applications in the development of novel anticancer, antioxidant and antimicrobial agents.